2005
DOI: 10.1534/genetics.104.034132
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evolution of the Vertebrate Myb Gene Family

Abstract: The duplication of genes and genomes is believed to be a major force in the evolution of eukaryotic organisms. However, different models have been presented about how duplicated genes are preserved from elimination by purifying selection. Preservation of one of the gene copies due to rare mutational events that result in a new gene function (neofunctionalization) necessitates that the other gene copy retain its ancestral function. Alternatively, preservation of both gene copies due to rapid divergence of codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 78 publications
(13 reference statements)
6
47
0
Order By: Relevance
“…These observations suggest that during the evolution of nematodes, there was a selection for a decoupling of Myb and the remaining members of the Myb-MuvB/dREAM complex. We have previously shown that vertebrate B-Myb can complement cell cycle defects in a Drosophila Myb-null mutant (41). Consistent with this observation, others have shown that vertebrate B-Myb is present in a complex together with the homologs of the MuvB core complex (42)(43)(44).…”
Section: Discussionsupporting
confidence: 68%
“…These observations suggest that during the evolution of nematodes, there was a selection for a decoupling of Myb and the remaining members of the Myb-MuvB/dREAM complex. We have previously shown that vertebrate B-Myb can complement cell cycle defects in a Drosophila Myb-null mutant (41). Consistent with this observation, others have shown that vertebrate B-Myb is present in a complex together with the homologs of the MuvB core complex (42)(43)(44).…”
Section: Discussionsupporting
confidence: 68%
“…Drosophila has a single myb gene (Dm-myb) that has been implicated in cell proliferation and in controlling the activity of certain origins of DNA replication (Katzen et al, 1998;Beall et al, 2002;Fitzpatrick et al, 2002). Recent work has shown that B-myb, but not A-myb or c-myb, is able to complement a defective Dm-myb gene (Davidson et al, 2004), suggesting a unique and probably ancestral function for B-myb, which cannot be complemented by other vertebrate myb family members.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, there are three Myb family members: A-Myb, B-Myb, and c-Myb (4). Drosophila has a single Myb gene-the functional ortholog of B-Myb (5,6).…”
mentioning
confidence: 99%